MODEL PENGEMBANGAN PERMAINAN FUN HOCKEY PADA SISWA KELAS XI SMA NEGERI 1 BAWANG KECAMATAN BAWANG KABUPATEN BATANG TAHUN 2014. (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to produce a model of the development of the game Fun Hockey in the XI student class of SMAN 1 Bawang, Bawang Subdistrict, Batang. The method used is the development of Borg & Gall, namely: (1) to analyze the products that will be developed that are obtained from the information collection, including field observations and study of literature, (2) develop a form of initial product model game Fun Hockey, (3) expert validation test which uses a physical education expert (hockey skills) and learning experts physical education in high school, as well as small scale test, using questionnaires and consultations later in the analysis, (4) the first product revision, revision of the product based on the results of expert evaluation and testing of small-scale (12 students), (5) field trials (28 students), (6) the revision of the final product is done based on the results of field trials, (7) the outcome Fun Hockey game for students of XI class generated through the revision of field trials. From the data on the differences can concluded that the Fun Hockey Game model development can be implemented as an alternative model for students learning physical education XI class SMAN 1 Bawang, Bawang Subdistrict, Batang